Socioeconomic Impact of Out-Migration in Beldandi Rural Municipality (Sudurpaschim Spectrum, 2024)
This study focuses on Navjyoti tole in Beldandi rural municipality-1 in Kanchanpur district, with the objectives of finding out the social economic impact due to rural out-migration of the entire tole. The tole currently houses 155 households and 612 individuals, according to the Beldandi rural municipality household survey in 2075. Forty-five out-migrant households were selected using a census approach for the study. Methodologically, the study combines exploratory and descriptive approaches, aiming to reveal the characteristics of rural out-migrants and understand the socioeconomic impacts of rural out-migration. It employs a mixed-method approach, incorporating both quantitative and qualitative techniques, alongside statistical methods for analysis. Migration from rural areas significantly affects the socioeconomic dynamics of households. This research examines its impact on households in the Beldandi rural municipality. Data from migrating households were gathered through surveys and interviews. The study reveals diverse effects of migration, both economically and socially. Financially, remittances from migrants enhance household income and living standards, yet they can lead to dependency on migrant earnings and decreased local productivity. Socially, migration alters family structures, impacting care, emotional support, and community cohesion. The absence of migrants strains community networks and traditions. Policy implications stress the need for comprehensive strategies leveraging the positive aspects of migration while mitigating slows negative effects. Community initiatives to strengthen local economies and support systems are recommended to counter the adverse effects of migration on households in the Beldandi Rural Municipality.